Решите уравнение (х^2-1)^2+(х^2-6х-7)^2=0

Решите уравнение (х^2-1)^2+(х^2-6х-7)^2=0
Гость
Ответ(ы) на вопрос:
Гость
[latex](x^2-1)^2+(x^2-6x-7)^2=0[/latex] [latex]((x-1)(x+1))^2+((x-7)(x+1))^2=0[/latex] [latex](x-1)^2(x+1)^2+(x-7)^2(x+1)^2=0[/latex] [latex](x+1)^2((x-1)^2+(x-7)^2)=0[/latex] [latex](x+1)^2(x^2-2x+1+x^2-14x+49)=0[/latex] [latex](x+1)^2(2x^2-16x+50)=0[/latex] [latex]2(x+1)^2(x^2-8x+25)=0[/latex] [latex](x+1)^2(x^2-8x+25)=0[/latex] [latex](x+1)^2=0[/latex]          или          [latex]x^2-8x+25=0[/latex] [latex]x+1=0[/latex]             или             [latex]D=(-8)^2-4*1*25\ \textless \ 64-100\ \textless \ 0[/latex] [latex]x=-1[/latex] Ответ: -1
Не нашли ответ?
Ответить на вопрос
Похожие вопросы